Otimização pelo método dos algoritmos genéticos e dimensionamento de estruturas tubulares metálicas espaciais com barras cruzadas para coberturas - Souza Junior, Dogmar Antonio de (2005)
The goal of this work is to evaluate the global mechanical behavior for three dimensional structure formed by circular hollow sections. The structure is represented by crossed tubular members. All the evaluations had been made by a computational program OTR developed specifically to optimize the structure. For carrying out the analyses, it was defined as objective function, the consumption of tubes of the covered plans. During the optimization, for the individual better adapted to the problem, the software generates the geometric mesh, loads on the structure e determines the displacements e the member forces. After that, all these parameters are checked according to the Brazilian code from the NBR8800 (ABNT, 1986). In this way, it can be gotten important conclusions concerning to the global mechanical behavior of the structure from the results of the optimization. Several structures with different configurations was evaluated, varying the geometric mesh, the relation length/width of the covered area, use or not of steel tie rod connecting supports and either the amount and location of supports along the length. Finally, a comparative study between the structural model considered e the model of the plane truss was done. The results had shown that software OTR is an excellent tool for analysis of reticulated structures, and easily can be adapted to different problems. It is also concluded that the tubular steel structures with crossed members for roofs are competitive in terms of economic if compared to the other structural systems.